PENAMBAHAN TRAKSI MANUAL PADA PEMBATASAN LINGKUP GERAK SENDI (LGS) DENGAN INTERVENSI ULTRASOUND (US) DAN RANSCUTANEOUS ELECTRIKAL NERVE STIMULATION (TENS) DAPAT MENINGKATKAN LINGKUP GERAK SENDI (LGS) ROTASI INTERNAL PADA PASIEN FROZEN SHOULDER - I Made Hartha Jaya Negara (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2013)
Frozen shoulder is a syndrome or condition with attacks of pain and limitation of active and passive motion with an uncertain cause / idiopathic often experienced by people aged 40-60 years and had a history of trauma. Causes for auto immobilization response to local tissue damage results repetitive injury, diabetes mellitus, paralysis, post breast surgery and myocardial infarction or chest, of the glenohumeral joint (bicipitalis tendonitis, rotator cuff inflammation, fracture) or extra-articular disorders (cervical spondylisis, angina pectoris). The main purpose of writing this paper to determine the diff addition of manual traction therapy restrictions LGS, the US. and with US, TENS, TENS for the increase in internal rotation in LGS patients soulder frozen. The research was conducted at the Poly Clinic Physiotherapy Public Hospital Sanglah Denpasar and Mutiara Medika Clinic on May 2011 until September 2011. The problems examined in this study was limited range of motion due to internal sendirotasi Frozen Shoulder is measured using a Goniometer. The research was divided into two groups: a control group and treatment group. The control group was given ultrasound and TENS treatment group was given intervention ultrasound, TENS and Manual Traction in the restricted range of motion data processing and data analysis using statistical program for science program (SPSS 13.0). By hypothesis testing using the Mann-Whitney test derived p-value = 0.000 (p value